Blood Safety Status in WHO African Region Countries: Lessons Learnt from Mauritius. (17th October 2017) - Loua, André; Sonoo, Janaki; Musango, Laurent; Nikiema, Jean Baptiste; Lapnet-Moustapha, Thomas
Abstract : In 2001, the WHO Office for Africa adopted a strategy for blood safety defining four targets. This paper describes the progress made by Mauritius in the implementation of this strategy. The blood safety indicators were collected and compared with the norms recommended by WHO. The country has formulated its blood policy and developed a strategic plan for its implementation since 2004. The total number of blood donations increased from 31, 228 in 2002 to 43, 742 in 2016, giving an annual blood collection rate evolving from 26.3 per 1000 inhabitants in 2002 to 34.2 per 1000 inhabitants in 2016. The percentage of voluntary donations rose from 60% to 82.5%. Since 2002, all the blood units collected have been tested for the mandatory infectious markers. The Blood Transfusion Service has been certified ISO2008-9001 and nucleic acid testing has been introduced. The preparation of blood components increased from 60% to 98.2%. The most transfused blood components were red cell concentrates, platelet concentrates, and fresh frozen plasma. In addition to transfusion activities, there were other departments performing antenatal serology, tissue typing, special investigations, and reagent preparation. Despite the progress made, some challenges remain, namely, legal framework and haemovigilance system. A regulatory system for blood needs to be established.